Fuel economy optimization of diesel engine for plug-in hybrid electric vehicle based on equivalent operating points. (June 2022) - He, Hongwen; Shou, Yiwen; Wang, Hao
Abstract: The plug-in hybrid electric vehicle (PHEV) has been progressively penetrated in the urban public transport system for its special advantages of energy saving and emission reduction potential. In order to improve the fuel economy of PHEV engine, an optimization study on the engine control parameters is carried out and applied on a PHEV with a rule-based energy management strategy (EMS) in this paper. Firstly, the mathematical model of diesel engine is established on GT-Power platform to accurately reflect the fuel consumption characteristics of engine. Secondly, a control parameter optimization method based on engine equivalent operating point is proposed and four key engine control parameters are optimized by genetic algorithm (GA). Thirdly, the optimization and calibration of the PHEV engine is performed under ChinaCity driving cycle. The results show that the maximum reduction of engine brake specific fuel consumption (BSFC) on the optimal operation line is 3.56%, and the equivalent fuel consumption of PHEV under ChinaCity, WVUCITY and WVUSUB driving cycles is reduced by 2.62%, 2.24% and 2.05%, respectively. Highlights: A diesel engine fuel consumption model is established on GT-power platform from the perspective of engine mechanism. The engine control parameter optimization method based on equivalent operating point can significantly reduce engine BSFC. Calibrating the engine according to equivalent operating points can effectively improve the fuel economy of PHEV.